Pharmacokinetics Of Imidocarb In Normal And Febrile Dogs And Goats - Abdullah, Abdul Salam (1983)
Disposition kinetics of imidocarb , an antiprotozoan drug, was studied in normal and febrile dog sand goats . Fever was induced using E. coli endotoxin , Trypanosoma evansi and Infectious Bovine Rhinotracheitis (I BR) virus.The objectives of the study were to compare the disposition kinetics of imidocarb in ruminant and monogastrics pecies , and the influence of fever of different etiology on the disposition kinetics of this drug. The concentration of imidocarb in body fluids and tissues were measured by spectrophotometry.The disposition kinetics of imidocarb in normal and febrile dogs and goats can be adequately described by a two-compartment open model. The apparent volume of the central compartment , V,c was significantly lower (P<0.01) but the volume of distribution, V d(area) was significantly higher (P<0.05) in normal goats than in dogs.Higher volume of distribution and the ratio of imidocarb level in peripheral- to-central compartment in goats ( 6:1 ) prolonged elimination of the drug, resulting in considerably higher levels of the drug still present in the tissues 14 days after a single subcutaneous or intramuscular dose.